2015
DOI: 10.1111/cxo.12267
|View full text |Cite
|
Sign up to set email alerts
|

Effect of retinal defocus on basketball free throw shooting performance

Abstract: Background: Vision plays a critical role in athletic performance; however, previous studies have demonstrated that a variety of simulated athletic sensorimotor tasks can be surprisingly resilient to retinal defocus (blurred vision). The purpose of the present study was to extend this work to determine the effect of retinal defocus on overall basketball free throw performance, as well as for the factors gender, refractive error and experience. Methods: Forty-four young adult participants of both genders were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 24 publications
6
35
2
Order By: Relevance
“…Using the pinhole, one quarter of participants in whom clinical visual measures were gathered showed an improvement in distance visual acuity of one line or more on the ETDRS chart ( Table 4 ) which strongly suggests that, in these individuals, better VA may be achieved with appropriate (or more appropriate) visual correction. While some athletes may perform at a high level even with reduced VA [ 58 ], given the often large distance between the official and the play, sub-optimal VA could have a detrimental effect on the ability to gather the information needed to reach the correct decision. About 18% of the participants had an inter-eye difference in distance visual acuity of one line or more of the ETDRS chart, suggesting that these officials could benefit from a new or updated optical prescription for use on the pitch.…”
Section: Resultsmentioning
confidence: 99%
“…Using the pinhole, one quarter of participants in whom clinical visual measures were gathered showed an improvement in distance visual acuity of one line or more on the ETDRS chart ( Table 4 ) which strongly suggests that, in these individuals, better VA may be achieved with appropriate (or more appropriate) visual correction. While some athletes may perform at a high level even with reduced VA [ 58 ], given the often large distance between the official and the play, sub-optimal VA could have a detrimental effect on the ability to gather the information needed to reach the correct decision. About 18% of the participants had an inter-eye difference in distance visual acuity of one line or more of the ETDRS chart, suggesting that these officials could benefit from a new or updated optical prescription for use on the pitch.…”
Section: Resultsmentioning
confidence: 99%
“…Erickson summarised information from several authors who advocated the benefits of correcting low refractive errors. Bulson et al demonstrated that small to moderate (1.50 D to 3.00 D) amounts of spherical myopic retinal defocus did not adversely affect basketball free throw shooting performance. The authors considered it likely that a basketball free throw is more resilient to retinal defocus than a basketball shot taken during live competition, because it represents a relatively non‐dynamic, non‐interactive task at a fixed distance.…”
Section: Discussionmentioning
confidence: 99%
“…Mann and colleagues [ 25 , 26 ] found that low-to-moderate levels of simulated myopia did not affect cricket batting and there are other examples of resistance to defocus in other interceptive tasks [ 71 ] and in other sporting tasks (e.g. basketball [ 23 ], golf [ 24 ]). One interpretation of such findings, and of ours, is that while good or excellent vision may be desirable for elite sports, it may not be essential.…”
Section: Discussionmentioning
confidence: 99%
“…Mansoor Ali Khan (1941–2011) became the captain of the Indian cricket team at the age of 21 having lost sight in one eye when aged 16 [ 21 ], and there are also questions about the vision of the legendary Babe Ruth [ 22 ]. Secondly, low to moderate levels of retinal-image blur, simulating uncorrected myopia, may not necessarily impact negatively on performance in sporting tasks [ 23 , 24 ], even in tasks where the visual demands are high [ 25 – 27 ]. Also, the uptake of eye care amongst elite-level athletes may be low; hence, suboptimal vision (e.g.…”
Section: Introductionmentioning
confidence: 99%